Construction of a micro-hydroelectric generator based on a lower intake crossflow turbine (MASKAY, 2024)
The study focuses on developing a micro-hydroelectric generator using a bottom inlet cross-flow turbine that takes advantage of the hydraulic potential of irrigation canals. The methodology used is quantitative and experimental and is based on a flow chart describing the stages from the creation to the implementation of the prototype. Variables such as water height and flow, as well as the dimensions of the irrigation canal, which could not be modified due to the agricultural activities carried out at the site, were taken into account. The results obtained from the field implementation of the designed prototype show that the generator can reach a power value of 93 W with an efficiency percentage of 11.3%, which sustainably produces energy in remote areas. In conclusion, the study highlights the need to explore new renewable and sustainable energy sources in response to the current energy crisis affecting society; it emphasizes the need to adopt cleaner energy alternatives that limit dependence on non-renewable resources while controlling the adverse effects of climate change.
Keywords: Flow; Hydroelectric; Micro-generator; Turbine; Water flow